Breast feeding and child behaviour in the Millennium Cohort Study. Issue 7 (9th May 2011) - Heikkilä, Katriina; Sacker, Amanda; Kelly, Yvonne; Renfrew, Mary J; Quigley, Maria A
Abstract : Objective: To examine whether breast feeding is associated with behavioural development in children aged 5 years. Design: The authors used data from a large, prospective, nationally representative UK cohort, the Millennium Cohort Study. Participants: 10 037 mother–child pairs from white ethnic background (9525 term and 512 preterm children) were included in the analyses. Methods: Duration of breast feeding (at all or exclusively) was ascertained from parental interview at study baseline, when the children were aged 9 months. Child behaviour was assessed using a parent-completed questionnaire, the Strengths and Difficulties Questionnaire (SDQ). The authors used logistic regression to investigate the associations of breastfeeding duration with abnormal parent-rated SDQ total and subscores at age 5 in term and preterm children separately. Results: Abnormal SDQ scores were less common in term children (n=1129/9525, 12%) than pre-term (n=78/512, 15%) children. Term children breast fed for 4 months or longer (n=2741/9525, 29%) had lower odds of an abnormal total SDQ score (multivariable-adjusted OR compared with never breastfed children (n=3292/9525, 35%) 0.67, 95% CI: 0.54 to 0.83). This effect was similar for all the SDQ subscores. In preterm children, longer duration of breast feeding was generally associated with lower odds of abnormal SDQ total and subscores but the effect estimates were imprecise. The associations between exclusive breast feeding and abnormal SDQ scores were similar to those of any breast feeding and abnormal SDQ scores. Conclusions: The findings suggest that, at least in term children, longer duration of breast feeding is associated with fewer parent-rated behavioural problems in children aged 5 years.